Fixed points of multivalued nonexpansive maps - T. Husain; Abdul Latif (International Journal of Mathematics and Mathematical Sciences)
Fixed point theorems for multivalued contractive-type and nonexpansive-type maps on complete metric spaces and on certain closed bounded convex subsets of Banach spaces have been proved. They extend some known results due to Browder, Husain and Tarafdar, Karlovitz and Kirk.